Who discovered the Lake Vostok? - V. Kotlyakov M.; V. Krenev A.; В. Котляков М.; В. Кренёв А. (Ice and Snow, 2016)
A history of the subglacial lake Vostok that had been revealed near this Soviet Antarctic Station is briefly described in the paper. Three participants of the Soviet Antarctic Expeditions played a significant part in the history of the Lake discovery, and they were a navigator of polar aviation R.V. Robinson, a physicist I.A. Zotikov, and a geographer A.P. Kapitsa. R.V. Robinson was the first man who had indicated to evidence of a subglacial lake in contours of the glacier surface; I.A. Zotikov had substantiated a hypothesis of a subglacial melting in central regions of the Antarctic continent and possible presence of water bodies in depressions of the glacier bed; A.P. Kapitsa had obtained by means of seismic sounding the original reflections which were later interpreted as reflections from subglacial water layer. And lastly, in some time later, the Britain glaciologist G. Robin had performed the thorough radio sounding in the vicinity of the Vostok station and finally proved existence of a large subglacial water body in this region. Further on, the lake was investigated by many participants of the Russian Antarctic Expeditions, as well as by scientists from the Britain Scott Institute and members of the American Antarctic Expeditions. Now this is the largest and the mostly studied subglacial lake in the Antarctica among almost 400 similar lakes revealed under the ice sheet. Изложена история открытия подледникового озера Восток, обнаруженного в районе одноимённой советской антарктической станции. В истории открытия озера главное значение имеют три имени участников советских антарктических экспедиций: штурмана полярной авиации Р.В. Робинсона, физика И.А. Зотикова и географа А.П. Капицы. Дальнейшие исследования озера выполнены многими участниками Российских антарктических экспедиций, учёными Британского полярного института имени Р. Скотта и членами американских антарктических экспедиций. Сейчас это самое крупное и наиболее изученное подледниковое озеро в Антарктиде из почти 400 таких же озёр, обнаруженных под ...